IDENTIFIKASI JAMUR DERMATOFITA PADA HELM DRIVER OJEK ONLINE DI KOMUNITAS SAUDARA SATU ASPAL (SASPAL) KOTA BENGKULU - heru laksono; Zahrah Nur Fitri; Guntur Baruara; Teddy Febriyanto (Poltekkes Kemenkes Bengkulu, 2026)
Dermatophytes are a group of pathogenic fungi that cause dermatophytosis by infecting keratin-rich tissues such as skin, hair, and nails. Helmets, particularly those used by online motorcycle taxi drivers, have the potential to become a transmission medium for these fungi due to frequent use and poor hygiene maintenance. This study aims to determine the presence of dermatophyte fungi on helmets used by drivers in the Saudara Satu Aspal (SASPAL) Community in Bengkulu City. A descriptive observational method was employed, with total population sampling. Samples were taken from 20 helmets using the swab method on the inner part and straps. The results showed that 17 out of 20 helmet samples (42.5%) were positive for dermatophytes, with 10 samples testing positive from the strap area and 7 from the inner helmet. Identified dermatophyte genera included Microsporum sp. and Trichophyton sp. These findings suggest that helmets can be a source of dermatophytosis infection, emphasizing the need for regular helmet hygiene among drivers.